2020
DOI: 10.15407/agrisp7.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of factors of managing productive processes of winter wheat in the Forest-steppe

Abstract: Aim. To study the impact of complex preparations, containing humic, fulvic and ulmic acids in combination with herbicides and nitrogen fertilizers, on winter wheat yield. Methods. Field, laboratory, statistical methods. Results. The impact of herbicides with different active substances and their mixtures with humic preparations Humifi eld and Foliar concentrate on weed infestation and productivity of Kryzhynka winter variety was investigated. It was determined that the application of herbicide Prima (400 g/ha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Therefore, fulvic acids are part of new biofertilisers. The highest efficiency is observed with the complex use of edaphic preparations for seed treatment, soil and foliar fertilization (Marenych et al, 2020). It was experimentally confirmed that humic fertilisers improved root growth, contributed to the formation of high-quality seedlings, and increased the yield of field crops (Savy et al, 2020).…”
Section: P I E C E S T H E T O T a L Le N Q T H O F T H E S E E D Li ...mentioning
confidence: 88%
“…Therefore, fulvic acids are part of new biofertilisers. The highest efficiency is observed with the complex use of edaphic preparations for seed treatment, soil and foliar fertilization (Marenych et al, 2020). It was experimentally confirmed that humic fertilisers improved root growth, contributed to the formation of high-quality seedlings, and increased the yield of field crops (Savy et al, 2020).…”
Section: P I E C E S T H E T O T a L Le N Q T H O F T H E S E E D Li ...mentioning
confidence: 88%
“…Однак, вирішити це питання за рахунок лише збільшення обсягів мінеральних добрив на сучасному етапі розвитку аграрного виробництва не доцільно: з одного боку це призведе до забруднення навколишнього середовища (лише близько 47-50 % внесеного азоту поглинається культурою протягом вегетаційного періоду [11], все інше потрапляє в навколишнє середовище у вигляді нітратів (NO3−), що вимиваються у гідросистеми, аміаку (NH3) та закису азоту (N2O), які забруднюють атмосферу та ґрунти [12], з іншого боку -надмірне використання мінеральних добрив не завжди є корисним для рослини. Саме тому обов'язковим етапом технологій виробництва пшениці озимої стало впровадження стимуляторів росту [13], що дає можливість зменшувати дози застосованих добрив, тим самим обмежити негативний вплив на навколишнє середовище, особливо при застосуванні стимуляторів росту природного походження, до яких належать багаточисленні гумінові препарати [14,15].…”
Section: вступunclassified
“…Отже, для отримання високих і стійких урожаїв пшениці озимої необхідним фактором є керування ростом і розвитком культур за допомогою відповідних агротехнічних заходів [19,20], які включають оптимальні способи живлення культури з використанням препаратів природного походження, що дозволяє отримувати екологічно чисту продукцію і зменшити негативний вплив на навколишнє середовище.…”
Section: вступunclassified